Leading the Internal Audit Function - Fountain, Lynn (Internal audit and IT audit., 2016)
While the Institute of Internal Auditors (IIA) has provided standards and guidelines for the practice of internal audit through the International Professional Practice Framework (IPPF), internal auditors and Chief Audit Executives (CAEs) continue to experience difficulties when attempting to balance the requirements of the IPPF with management expe.